NOT JUST WHITE: COLOGNE FABRICS - C. Höpken, Constanze C. (Rei Cretariae Romanae Fautorum Acta, 2024)
In Cologne forty four excavated sites have revealed evidence for more than thirty pottery production workshops with about a hundred kilns. The workshops were established in Cologne as a result of the expanding market in and around the city, as well as the transportation of the finished products to other markets via long distance roads or along the Rhine. Most of the workshops are dated to the first and second centuries, another two to the third and fourth centuries AD. Production was comprised of colour coated, Gallo-Belgic, plain and coarse wares along with dolia and mortaria. In some work- shops a small amount of Terra sigillata, Terra sigillata imitations, “Weißrotware”, mica dusted and glazed wares were made.